2019
DOI: 10.1101/704106
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defining how oncogenic and developmental mutations ofPIK3R1alter the regulation of class IA phosphoinositide 3-kinases

Abstract: The class IA PI3Ks are key signalling enzymes composed of a heterodimer of a p110 catalytic subunit and a p85 regulatory subunit, with PI3K mutations being causative of multiple human diseases including cancer, primary immunodeficiencies, and developmental disorders.Mutations in the p85α regulatory subunit encoded by PIK3R1 can both activate PI3K through oncogenic truncations in the iSH2 domain, or inhibit PI3K through developmental disorder mutations in the cSH2 domain. Using a combined biochemical and hydrog… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
2
0
0
Order By: Relevance
“…We further demonstrated that most or all of the mutant p85α expressed is not bound to p110α, while unbound mutant p85α still binds to Irs1/2, effectively competing with PI3K holoenzyme. The observation that p85α ΔEx11 can associate with Irs1/2 is in agreement with reports that p85α ΔEx11-containing PI3Kα and PI3Kδ can be stimulated by pY2-peptides (Dornan et al, 2017;Dornan et al, 2020) and that p85α ΔEx11 is recruited to tyrosine-phosphorylated LAT in T cells (Lucas et al, 2014b). The competition we suggest between unbound mutant p85α and PI3K holoenzyme for binding to the activated RTKs is in keeping with longstanding evidence that free p85 downregulates PI3K signalling through the same competitive mechanism (Thorpe et al, 2017;Ueki et al, 2002), with a single study suggesting in addition that overexpression of tagged p85α leads to Irs1 sequestration with free p85α in cytosolic foci where PI(3,4,5)P3 production does not occur (Luo et al, 2005) The current study has limitations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We further demonstrated that most or all of the mutant p85α expressed is not bound to p110α, while unbound mutant p85α still binds to Irs1/2, effectively competing with PI3K holoenzyme. The observation that p85α ΔEx11 can associate with Irs1/2 is in agreement with reports that p85α ΔEx11-containing PI3Kα and PI3Kδ can be stimulated by pY2-peptides (Dornan et al, 2017;Dornan et al, 2020) and that p85α ΔEx11 is recruited to tyrosine-phosphorylated LAT in T cells (Lucas et al, 2014b). The competition we suggest between unbound mutant p85α and PI3K holoenzyme for binding to the activated RTKs is in keeping with longstanding evidence that free p85 downregulates PI3K signalling through the same competitive mechanism (Thorpe et al, 2017;Ueki et al, 2002), with a single study suggesting in addition that overexpression of tagged p85α leads to Irs1 sequestration with free p85α in cytosolic foci where PI(3,4,5)P3 production does not occur (Luo et al, 2005) The current study has limitations.…”
Section: Discussionsupporting
confidence: 93%
“…Wild-type and SHORT syndrome mutant holoenzymes were successfully purified for in vitro assay, but despite multiple attempts, ΔEx11 holoenzyme could only be made in small amounts under identical conditions, and moreover was unstable on storage, precluding further study. In keeping with previous reports (Chudasama et al, 2013;Dornan et al, 2017;Dornan et al, 2020), p85α R649W showed severely reduced phosphotyrosine-stimulated activity in complex with p110α, with highly significant but lesser loss of function seen for Y657X and E489K (Fig 3A,Fig EV5A). No increase in basal activity was seen for any variant.…”
Section: Effect Of Pik3r1 Mutations On Phosphoinositide 3-kinase Acti...supporting
confidence: 92%